The Effect of Social Media, Online Food Delivery Service (OFDS), Digital Wallet on the Progress of Micro, Small and Medium Enterprises (MSMEs) in Cirebon City - Karoma Nur Imaya; Anita Anita; Ramah Puji Astuti (International Journal of Business, Economics, and Social Development, 2025)
In this research, we look at how using Online Food Delivery Service (OFDS), social media, and digital wallets on progress of culinary Micro, Small, and Medium Enterprises (MSMEs) in Cirebon City. As digital technology develops, MSMEs are required to adapt to improve competitiveness and business sustainability. Using methods from multiple linear regression analysis, this study took a quantitative approach, involving 369 respondents from a total of 4,830 culinary MSMEs in Cirebon. According to the findings, all three factors significantly and favorably affect the development of MSMEs. Social media acts as an effective marketing tool to increase visibility and interaction with customers. OFDS facilitates consumer access to MSME products without the need for physical stores, thus expanding the market and improving distribution efficiency. Meanwhile, digital wallets simplify transactions, increase payment security, and help with financial record-keeping. With these findings, the study suggests that MSMEs should increasingly actively utilize digital technology to expand markets and improve operational efficiency. The implications of this research can serve as a reference for businesses, government, and digital service providers in support of MSME growth in the digital era.